2012
DOI: 10.1108/02640471211275756
|View full text |Cite
|
Sign up to set email alerts
|

Semantic annotation and retrieval of documentary media objects

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm: 412925 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Subsequently, MPEG-7 services convert the XML of the content of the video mapping and annotated segments into RDF ( Figure 5). This conversion considers the Rhizomik MPEG-7 to RDF mechanism presented by Kanellopoulos et al [30].…”
Section: ) Mpeg-7 Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, MPEG-7 services convert the XML of the content of the video mapping and annotated segments into RDF ( Figure 5). This conversion considers the Rhizomik MPEG-7 to RDF mechanism presented by Kanellopoulos et al [30].…”
Section: ) Mpeg-7 Servicesmentioning
confidence: 99%
“…The analysis of the results obtained showed that for AvaOne users, the participants of this study, both ''Student'' profile and ''Teacher'' profile the embedding of metadata into educational videos through related descriptors facilitates and defines the search and access to specific contents in these videos, according to the interest of the users of this portal, which validates the hypothesis of this study, that brings as contributions a real, scalable, flexible solution, and allows the reuse of segments of educational videos at the architectural or semantic level. This evaluation made it possible to validate the adequacy of concepts, technologies and methodologies presented in literature [6], [25], [26], [28], [30], [36], [37], in the construction of an educational semantic portal prototype that enables the embedding of metadata into educational videos.…”
Section: Final Considerationsmentioning
confidence: 99%
“…For example, research efforts based on the MPEG-7 standard (MPEG-7, 2004) allow enriching media content with semantic content annotations, which in turn facilitate new forms of multimedia experience such as semantic-based content selection and filtering. Unfortunately, only a few projects have exploited the extended metadata annotation possibilities available with the new MPEG standards (Martinez et al, 2002;Kanellopoulos, 2012).…”
Section: Multimedia Representation Approachesmentioning
confidence: 99%
“…Para a adição de semântica aos conteúdos da Web tem-se utilizado tecnologias desenvolvidas para dar significado e promover a interação entre diversos sistemas (KANELLOPOULOS, 2012). Os portais web tradicionais auxiliavam a permuta de conteúdos entre grupos de pessoas e se fizeram populares.…”
unclassified
“…Estudos como Alan et al (2008); Sebastine; Thuraisingham e Prabhakaran (2010); Kanellopoulos (2012); Lachtim (2008); Silva e Gluz (2012); Patrocinio e Ishitani (2009) mostram que, de forma análoga ao modelo da programação orientada a objetos, objetos de aprendizagem com anotação semântica apropriada podem ser armazenados em repositórios de forma a serem reutilizados e referenciados no contexto educacional. Neste estudo, toma-se como pressuposto que os recursos audiovisuais são instrumentos de amplas possibilidades de utilização em diferentes áreas, dentre as quais a educação.…”
unclassified